Effect of a booster-dose of rabies vaccine on the duration of virus neutralizing antibody titers in bovines - Albas,Avelino (1998)
Humoral immune response using inactivated rabies vaccine was studied in 35 nelore cross-bred bovines of western region of São Paulo state. Ninety days after vaccination, 13 (92.8%) animals presented titers 30.5IU/ml, through mouse neutralization test. After 180 days, 9 (64.3%) sera showed titers 30.5IU/ml, after 270 days, only one (7.1%) showed a titer of 0.51IU/ml, and after 360 days, all animals showed titers < 0.5IU/ml. Group of animals receiving booster dose 30 days after vaccination presented, two months after, all with titers > 0.5IU/ml. At 180 days, 17 (80.9%) sera presented titers > 0.5IU/ml; at 270 days, 15 (71.4%), with titers 30.5IU/ml and at 360 days, 4 (19.0%), with titers 30.5IU/ml. Booster-dose ensured high levels of neutralizing antibodies for at least three months, and 240 days after revaccination, 71.4% of animals were found with titers 30.5IU/ml.